2016
DOI: 10.1016/j.neurobiolaging.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

The APOE paradox: do attentional control differences in mid-adulthood reflect risk of late-life cognitive decline

Abstract: Article (Accepted Version) http://sro.sussex.ac.uk Lancaster, Claire, Tabet, Naji and Rusted, Jennifer (2016) The APOE paradox: how do attentional control differences in mid-adulthood reflect risk of late-life cognitive decline. Neurobiology of Aging, This version is available from Sussex Research Online: http://sro.sussex.ac.uk/62415/ This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If you wish to cite this item you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Recently, it has been shown that younger carriers of ε 2 allele have more gray matter in the hippocampus and rely more on hippocampal-dependent strategies in tasks of navigation than noncarriers (Konishi et al., 2016). In contrast, other studies have found performance disadvantages in attention-related tasks in ε 2 carriers in middle and old age, compared with ε 3 carriers (Lancaster et al., 2016, Lancaster et al., 2017). Considering these complicated effects of the APOE ε 2 allele on cognitive performance, future studies should aim to examine the role of all APOE alleles on behavior, across aging, to provide a more comprehensive phenotypical description of this gene on behavior and its relationship with AD.…”
Section: Discussionmentioning
confidence: 56%
“…Recently, it has been shown that younger carriers of ε 2 allele have more gray matter in the hippocampus and rely more on hippocampal-dependent strategies in tasks of navigation than noncarriers (Konishi et al., 2016). In contrast, other studies have found performance disadvantages in attention-related tasks in ε 2 carriers in middle and old age, compared with ε 3 carriers (Lancaster et al., 2016, Lancaster et al., 2017). Considering these complicated effects of the APOE ε 2 allele on cognitive performance, future studies should aim to examine the role of all APOE alleles on behavior, across aging, to provide a more comprehensive phenotypical description of this gene on behavior and its relationship with AD.…”
Section: Discussionmentioning
confidence: 56%
“…The inconsistent null pattern in some studies may derive from methodological issues, including differences in age, cognitive measures, sample size, and other cognitive risk factors [36,48]. It is noteworthy that the differential effects of APOE ε4 on cognition during different life stages represents an example of antagonistic pleiotropy [63]: a reduced or null negative effect is observed in middle age [50,64]; a reversed positive effect is observed in young adults [49]; and the effect size in the elderly is also affected by age [48]. Thus, any APOE -related study must take into account the interaction between age and the APOE gene.…”
Section: The Effects Of the Apoe Gene On Cognitive Function And Dementioning
confidence: 99%
“…The AP effect of APOE suggests that it would be fundamental to precisely define the specific periods of life to investigate and in which of those periods AP effects take place [145]. In fact, during earlier periods of life, the deleterious effects of APOE 4 vs. APOE 2 appear to be paradoxically reversed in some cases in respect to older age [31,129,146,147]. Although studies focusing on the allelic effects of APOE on young adults and children are relatively rare, a series of recent analyses evidenced an increased risk for poorer outcomes in APOE 2- vs. APOE 4-carriers in pediatric populations [130].…”
Section: Apoe Polymorphism In Normal and Pathologic Conditions Of Thementioning
confidence: 99%
“…language). Furthermore, we succinctly describe some of the possible molecular mechanistic aspects and biochemical pathways that have been proposed to explain the apparently paradoxical effects of APOE across the human lifespan [31].…”
Section: Introductionmentioning
confidence: 99%